Factors affecting the performance of Tshiombo Irrigation Scheme in Limpopo Province, South Africa. - Mwadzingeni, Liboster; Mugandani, Raymond; Mafongoya, Paramu (Journal of Agribusiness and Rural Development, 2021)
Smallholder irrigation farming is valuable for improving the welfare of rural communities in South Africa. Irrigation schemes in South Africa perform below average as some collapsed. Boosting performance of irrigation schemes will ensure economic sustainability for low-income earners. There is little scholarly literature on factors affecting performance of smallholder irrigation schemes in South Africa. Therefore, this study assessed factors affecting yield and gross margin of sweet potato in Tshiombo Irrigation Scheme. Data was collected using structured questionnaires, Focus Group Discussions and in-depth interviews. Performance of the irrigation scheme was analysed using Ordinary Least Square. Yield or gross margin of sweet potatoes were used as proxies for scheme performance. Six estimators, namely age of farmers (-0.022), labour availability (-0.185), cultivated area (-0.130), pesticide subsidy (0.138), market price (6.090), and distance of the plot from the main canal (0.191) significantly impacted performance of the scheme. Minimum participation of farmers in value chain exposed then to lower market prices. Gross margin was generally low due to limited participation of aging farmers in the value chain. Performance of the scheme can be improved through providing and ensuring competitive prices and encouraging youth to participate in scheme farming by providing lucrative market prices.